Environmental monitoring using linden tree leaves as natural traps of atmospheric deposition: a pilot study in Transilvania, Romania - Braun, Mihály; Margitai, Zita; Tóth, Albert; Leermakers, Martine (Acta Geographica Debrecina Landscape & Environment series, 2007)
Atmospheric pollution caused by toxic elements is an emerging problem of concern. Tree leaves have been widely used as indicator of atmospheric pollutions and they are effective alternatives to the more usual biomonitoring methods. Tree leaves can be used as natural traps of atmospheric deposition. Elemental composition of dust deposited onto leaf surfaces can be used to characterize the urban environment. A pilot survey including 16 Romanian settlements was carried out in order to evaluate the characteristics and sources of air pollutants. Tree leaves (Tilia tomentosa, Tilia cordata, Tilia platyphyllos) were collected and used for the measurements. Elemental analyses were carried out by ICP-OES and ICP-MS. Principal component and discriminant analyses were used to characterizing and estimating the level of pollution. Settlements were grouped on the basis of discriminant function values. Multivariate comparison of chemical data ordered the settlements into 3 main groups, which showed a systematic geographic distribution.